Diabetes mellitus treatment using herbal drugs - Sonia Verma; Madhu Gupta; Harvinder Popli; Geeta Aggarwal (International Journal of Phytomedicine, 2018)
Diabetes mellitus is becoming a common metabolic disorder which has serious threat to public health in the world. There are chemicals and biochemical agent that helps in controlling diabetes but there is no permanent remedy available which helps to get recovered completely from this disorder. By conducting large number of research work, numerous traditional medicines have been found for diabetes. Substances and extracts isolated from different natural resources especially plants have always been a rich arsenal for controlling and treating diabetes problem and complication arising due to it. So this review helps the reader to understand the importance of various types of herbal and polyherbal formulations present traditionally which can be used to treat diabetes mellitus.